2011
DOI: 10.4037/ccn2011293
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Impella 2.5 in High-Risk Percutaneous Coronary Intervention

Abstract: The Impella 2.5 is a percutaneously placed partial circulatory assist device that is increasingly being used in high-risk coronary interventional procedures to provide hemodynamic support. The Impella 2.5 is able to unload the left ventricle rapidly and effectively and increase cardiac output more than an intra-aortic balloon catheter can. Potential complications include bleeding, limb ischemia, hemolysis, and infection. One community hospital’s approach to establishing a multidisciplinary program for use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In the US, several trials like Protect I, Protect II, ISAR-SHOCK, Recover I and Recover II trials have been sponsored by ABIOMED to help answer this questions with encouraging results [5]. It has also been shown that it can help improve coronary blood flow and cardiac output by reducing the workload and oxygen consumption of the cardiac muscle [10-12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, several trials like Protect I, Protect II, ISAR-SHOCK, Recover I and Recover II trials have been sponsored by ABIOMED to help answer this questions with encouraging results [5]. It has also been shown that it can help improve coronary blood flow and cardiac output by reducing the workload and oxygen consumption of the cardiac muscle [10-12].…”
Section: Discussionmentioning
confidence: 99%
“…It is able to achieve about 2.5 L/min of blood flow per cardiac output. The United States Food and Drug Administration approved this device in June 2008 for up to 6 hours of support [5]. However, in Europe, the device is approved for up to 5 days of partial circulatory support [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is approved by the Food and Drug Administration (FDA) for a total duration of 6 hours but has been used in some patients for as long as 2 weeks. The use of percutaneous LVAD devices are being used progressively more in high risk Percutaneous Coronary Intervention (PCI) procedures because they provide greater increases in cardiac output than IntraAortic Balloon Pumps (IABP) [7]. The IABP is limited in its ability to provide circulatory support and if left ventricular function is severely compromised, an IABP will not be effective [7].…”
Section: Discussionmentioning
confidence: 99%
“…The use of percutaneous LVAD devices are being used progressively more in high risk Percutaneous Coronary Intervention (PCI) procedures because they provide greater increases in cardiac output than IntraAortic Balloon Pumps (IABP) [7]. The IABP is limited in its ability to provide circulatory support and if left ventricular function is severely compromised, an IABP will not be effective [7]. The Impella  2.5 offers several advantages when compared to ECMO primarily being its ease of insertion in the catheterization laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Abiomed Impella pump, which is used to treat patients with cardiogenic shock, has helically shaped impeller blades and a standard stent with straight filaments. 2 The protective cage or stent around current intravascular pumps is not designed to maximize energy transfer but, rather, to minimize manufacturing effort. To improve flow control and energy transfer, we evaluated the inclusion of a uniquely shaped protective cage to advance the current state-of-the-art and create a new intravascular blood pump as a therapeutic option for patients with ailing singleventricle physiology.…”
mentioning
confidence: 99%